2022
DOI: 10.48550/arxiv.2201.06114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protecting fiber-optic quantum key distribution sources against light-injection attacks

Abstract: A well-protected and characterised source in a quantum key distribution system is needed for its security. Unfortunately, the source is vulnerable to light-injection attacks, such as Trojan-horse, laser-seeding, and laser-damage attacks. In particular, the latter attack can modify properties of components inside the source and open it up for the other attacks. Here we propose a countermeasure against the laser-damage attack, consisting of an additional sacrificial component placed at the exit of the source. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To see this, note, for instance, that if the power of Eve's injected light is limited to, say, 1 dBm [35][36][37], then to obtain a lower bound δ δ L ≈ 1-4 × 10 −8 (see appendix C)-which is already a relatively high value for long-distance QKD-it is necessary to consider about 140 dB of total isolation, which includes the effect of optical isolators, attenuators, the reflectivity of the optical elements, and other internal losses. Besides, note that since Eve's light has to make a round trip, the isolation provided by certain elements-e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To see this, note, for instance, that if the power of Eve's injected light is limited to, say, 1 dBm [35][36][37], then to obtain a lower bound δ δ L ≈ 1-4 × 10 −8 (see appendix C)-which is already a relatively high value for long-distance QKD-it is necessary to consider about 140 dB of total isolation, which includes the effect of optical isolators, attenuators, the reflectivity of the optical elements, and other internal losses. Besides, note that since Eve's light has to make a round trip, the isolation provided by certain elements-e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some experiments with continuous-wave lasers have shown that single-mode optical fibers are severely damaged if they are exposed to an average power of 2-5 W [12,33,34]. Moreover, this power limit may be lowered by using on-purpose devices as optical fuses [35], optical circulators and isolators [36], or other power limiting devices based on the thermo-optical defocusing effect [37]. In addition, one could also put a limit on the intensity of Eve's injected light by placing a monitor detector to abort the protocol if the input intensity surpass a predefined threshold.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a measurementdevice-independent (MDI) QKD protocol [13] is immune to all measurement-side secure loopholes, because this protocol does not make assumption on the measurement devices. Thus, the loopholes in the source unit are the last obstacle to achieve security of QKD in reality [8,9,[14][15][16]. The most effective solution to eliminate such security threat is to consider the practical imperfections of the source in the security model.…”
Section: Introductionmentioning
confidence: 99%